FREQUENCY OF HEPATITIS B AND C SEROPOSITIVITY AMONGST PATIENTS UNDERGOING HEMODIALYSIS - KHAN, I; RASHID, S; GHUMRO, S; HAQ, TU; KOUSAR, A; ZEB, H; ALI, A; ALI, S (Biological and Clinical Sciences Research Journal, 2024)
Hepatitis is caused by many viruses, but Hepatitis B and C viruses are the most harmful, showing a unique and noteworthy correlation between kidney disorders and hemodialysis in individuals. Objective: This study aimed to determine the frequency of hepatitis B and C seropositivity amongst hemodialysis individuals. Methods: This cross-sectional study was conducted at the Department of Medicine, Hayatabad Medical Complex Peshawar, after obtaining permission from the ethical board of the institute. The study duration was six months from August 2023 to January 2024. Individuals who were going to perform hemodialysis in the hospital during the study period were enrolled. Sixty-four chronic kidney disease patients were tested for anti-HBsAg and anti-HCV antibodies who visited our hospital for dialysis. All samples were tested for HBs antigen and anti-HCV antibodies using a more sensitive chemiluminescence assay (Vitros, Orthoclinical Technologies). Microsoft Excel was used for data entry, analysis, and interpretation. Results: A total of 64 participants who were going for hemodialysis were examined for seropositivity of hepatitis B and C viruses. The anti-HCV antibody was positive in 21 (32.8.0%) and 9 (14.0%) individuals who were positive for hepatitis B surface antigens. A significant portion of the individuals, 28 (43.75%), had dialysis of less than 50 times while 18 (28.1%) patients had dialysis of 50-100 times. On the other hand, the majority of the patients who tested positive for HCV (73.8%) and HBV (56.3%) also got HD 50 to 100 times. For HBV-infected individuals, the average dialysis stay was 27 months, but for HCV-infected ones, it took 30 months. For both HBV and HCV infections, the length of Hemodialysis revealed a vital risk factor (P < 0.05). Conclusion: It was concluded from the current study that the frequency of hepatitis B seropositivity was 14.0%, while that of hepatitis C was 32.8.0% among participants undergoing dialysis. Viral hepatitis is a severe health risk for hemodialysis patients, especially in underdeveloped nations.